PROSES PENYUSUNAN DOKUMEN PERENCANAAN DAN LAPORAN PERTANGGUNGJAWABAN PEMERINTAH DAERAH DI INDONESIA: PENDEKATAN KUALITATIF - Jovan Febriantoko; - - Febrianty (Trunojoyo University of Madura, 2017)
This study aims to provide an overview of the process of preparing and analyzing factors that become obstacles in the process of preparation of planning documents and accountability reports of local governments in Indonesia. The type of research to be used is qualitative research. The type of data in this study is based on primary data. Technique data collection used is interview. Interviews were conducted in depth with semi-structured questions. Selection of participants with expert analysis techniques. The data analysis technique is using coding which consists of open coding, axial coding and selective coding. The result of the research shows that the process of preparation of planning documents and accountability reports to the local government is still experiencing constraints in the stages of resource identification, evaluation is limited to the implementation, not showing results-oriented activities, and preparing accountability report due to obligations. The inhibiting factors were found in the presence of coordination difficulties that occurred between the fields within the organization and the inability to identify the problem being experienced.